Selective Embolization of Arteriovenous Malformation in Gross Hematuria Post-Renorrhaphy: A Case Report - Tangkilisan, Adrian; Sukanto, Wega; Paat, Rigel; Iskandar, Edward (Medical Scope Journal, 2025)
Abstract: Management approaches for renal trauma vary from conservative methods for contusions to surgical interventions for severe injuries. Postoperative renal artery embolization (RAE) is crucial to control bleeding and preserve renal parenchymal tissue integrity. We reported a patient presented with hematuria 30 minutes after sustaining a stab wound to the right waist, accompanied by severe pain, dizziness, and cold sweats. Physical examination revealed a penetrating wound in the right flank, gross hematuria, and signs of hypovolemic shock. The patient was diagnosed with grade II hypovolemic shock due to a renal laceration and duodenal rupture, initial resuscitation and conservative management were followed by exploratory laparotomy and renorrhaphy. Persistent gross hematuria post-renorrhaphy necessitated embolization. Hypovolemic shock resulted from significant bleeding from duodenal and renal lacerations. Renorrhaphy effectively minimized renal parenchymal damage without urine extravasation. Subsequent angiography revealed gross hematuria, indicating renal arteriovenous malformation (AVM). Embolization using a vortex coil successfully managed bleeding from large vessels and improved perfusion in the lesion area. In conclusion, renal trauma poses serious risks, including hypotension and hemorrhagic shock. Prompt resuscitation followed by surgical repair and angiographic embolization are essential. Embolization remains a generally safe and effective method for achieving selective hemostasis in such cases. Keywords: renal trauma; gross hematuria; renorrhaphy; renal-artery embolization